"Exotism" on display at La Specola Museum - Innocenti, Gianna (Tidsskrift for kulturforskning, 2010)
In Florence, "La Specola" Museum was first opened to the public in 1775, by order of the enlightened Grand Duke Peter Leopold of Lorraine who wished to put together all the "natural curiosities" from his collections, as well as from the Medici ones, in the context of an enlightened project of popular education. The zoological collections consisted of many Italian and foreign specimens, and among them on display were several amazing animals, peculiar for their provenance, rarity or dimension that gave rise to the social imagination of the Museum visitors. This paper provides a selection of the unusual animals on display and gives an account of their arrival at La Specola Museum as many specimens have a "story" to tell the visitor.